Stakeholders’ perception of factors influencing adoption of a pediatric weight management intervention: a qualitative study - Sierra-Velez, Desiree; Gundewar, Anisha; Persaud, Alicia; Simione, Meg; Castro, Ines; Perkins, Meghan; Lindros, Jeanne; Salmon, Jeremiah; Smith, Justin D.; Taveras, Elsie M.; Fiechtner, Lauren (Frontiers in Public Health, 2023)
Background Childhood obesity is highly prevalent in the United States and disproportionately impacts communities of color and low-income populations; these disparities have worsened during the COVID-19 pandemic. Adoption of effective pediatric weight management interventions (PWMIs) that have been evaluated among low-income diverse populations is needed. The Healthy Weight Clinic PWMI, a package co-developed by the American Academy of Pediatrics and Massachusetts General Hospital, helps health centers establish multidisciplinary Healthy Weight Clinics based on previous randomized controlled trials which demonstrated effectiveness. We sought to identify the factors influencing successful adoption of this PWMI and understand adaptations needed prior to implementation in new sites. Methods We interviewed 20 stakeholders, 10 from two health centers in Mississippi where the Healthy Weight Clinic PWMI will be piloted (pre-implementation sites) and 10 from health centers that have previously implemented it (sites in maintenance stages). Separate interview guides informed by the Consolidated Framework for Implementation Research (CFIR) were developed for the pre-implementation sites and those in maintenance stages, including questions related to adaptations of the PWMI in response to the COVID-19 pandemic. Qualitative data analysis was conducted using directed content analysis based on CFIR constructs. Adaptations in response to the pandemic were categorized using Framework for Reporting Adaptations and Modifications-Expanded (FRAME). Results In pre-implementation sites, an inner setting facilitator mentioned was a positive learning climate. Characteristics of individuals that can facilitate adoption include staff willingness to learn, valuing evidence-based care for childhood obesity, and culturally and weight-sensitive staff. In terms of patient needs and resources (outer setting), social drivers of health are barriers to adoption, but creative solutions were suggested to mitigate these. Other facilitators related to the intervention included its multidisciplinary model and adaptability. Similar themes were elicited from sites in maintenance stages; adaptations brought on by the pandemic, such as telehealth visits and content modification to align with distancing guidelines and the effects of social isolation were also described. Conclusion Understanding the factors influencing adoption of an evidence-based PWMI informs necessary adaptations and implementation strategies required to facilitate nationwide dissemination of PWMIs, with the goal of reaching the populations most at-risk.